PREVALENCE OF PSYCHIATRIC COMORBIDITIES IN PATIENTS WITH DEPRESSION - GUPTA, MEGHNA; SHARMA, PARUL; SHARMA, RAVI CHAND; YAKHMI, SAURABH (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objective: The aim of the study was to study the prevalence of psychiatric comorbidities in patients of depression. Methods: The present cross-sectional study was conducted among 60 patients of depression. All the patients were evaluated for sociodemographic profile and Mini International Neuropsychiatric Interview was administered to evaluate, identify, and diagnose the most common psychiatric comorbidities as per its modules. Results: Results showed that 65.0% of patients had psychiatric comorbidities and 35.0% had no psychiatric comorbidity. About 53.3% patients had psychiatric comorbidity of generalized anxiety disorder, 23.3% patients had psychiatric comorbidity of suicidality, 11.7% had panic disorders, 6.7% had alcohol use disorders, and 5.0% had substance use disorders (SUDs) (non-alcoholic). No statistically significant association was found in prevalence of different psychiatric comorbidities among sociodemographic characteristics of age, gender, region, religion, family type, educational status, and occupational groups. However, statistically significant association was seen among alcohol use disorders in different gender groups and occupational groups. Conclusion: Our study showed the highest prevalence of psychiatric comorbidity of generalized anxiety disorder and then suicidality, panic disorders, alcohol use disorders, and least prevalence of SUDs. No statistically significant association was found between sociodemographic characteristics and psychiatric comorbidities except association of alcohol use disorders with gender and occupational groups. There is a paucity of research exploring relationship of specific psychiatric comorbidities in depressive patients in India. Data of our study will contribute to enrich the Indian specific data on psychiatric comorbidities in depression and help formulate appropriate management strategies.